"Authentic" Dance and Racialized Ethnic Identities in Multicultural America: The Chinese in Minnesota and Peruvians in New Jersey. Issue 3 (July 2017) - Wilcox, Hui Niu; Busse, Erika
We investigate how Chinese and Peruvian immigrants in the United States construct the idea of authenticity through dance and what roles the discourse and practice surrounding authenticity play in the formation of racialized ethnic identities. This inquiry reveals that "authenticity" in the context of immigrant dance has two distinct but related dimensions; it is both a descriptor of cultural practice and a quality of individual subjectivities by which immigrants recognize the importance of dance for both cultural preservation and individual self-actualization. Additionally, through so-called authentic cultural practices such as dance, immigrants in the United States preserve their before-migration national identities. They do so in the institutional context of multiculturalism, where the host society's demands for authenticity converge with immigrants' desire for belonging and where immigrants experience racial formation and ethnic construction simultaneously.